2022
DOI: 10.1159/000525653
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Dose-Response Relationship? Real-World Outcomes of Anti-Vascular Endothelial Growth Factor Treatment in Neovascular Age-Related Macular Degeneration

Abstract: Purpose: To explore the dose-response relationship of anti-vascular endothelial growth factor (VEGF) agents, with bevacizumab as 1st line treatment, on visual acuity (VA) outcome during the first year of treatment in neovascular AMD (nAMD) patients in real-life conditions. Methods: A retrospective, observational, single center study at the Ophthalmology Division, Tel Aviv Medical Center. Inclusion criteria was naive AMD patients treated with anti VEGF injections between the years 2017-2020. Electronical medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In contrast to our findings, other studies have suggested that there is no correlation between age and number of injections. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, other studies have suggested that there is no correlation between age and number of injections. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our findings, other studies have suggested that there is no correlation between age and number of injections. 20,21 Further research may be necessary to conclusively determine whether and how age directly affects the number of anti-VEGF injections required to treat AMD.…”
Section: Correlation Between Age and Number Of Injectionsmentioning
confidence: 99%
“…Repeated injections are needed, that often result in low compliance and not all patients respond to the anti-VEGFA treatment. [42][43][44] Furthermore, there is currently no treatment for the dry form of the disease. Therefore, it is essential to develop safe, effective, and long-term treatments for this disease, given its high prevalence.…”
Section: Introductionmentioning
confidence: 99%